2012
DOI: 10.1097/inf.0b013e318267fd8b
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a 2-dose Regimen of a Combined Measles, Mumps, Rubella and Varicella Live Vaccine Manufactured With Recombinant Human Albumin

Abstract: The results confirm the good safety profiles of MMRV and of measles, mumps and rubella vaccines manufactured with recombinant human albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Indeed, data show that current varicella vaccine is immunogenic and well tolerated as early as 9 months of age. [23][24][25] For the protection of infants younger than 9 months of age, the vaccination should be considered for unprotected household members or any person in close contact with a pregnant woman or a very young baby. Additionally postpartum catch-up vaccination of susceptible persons is another the large number of subjects in each group, it is thus reasonable to believe that our results provide a true idea of the inverse correlation that may exist between passive immunity and severity of varicella complications in infants below one year of age.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Indeed, data show that current varicella vaccine is immunogenic and well tolerated as early as 9 months of age. [23][24][25] For the protection of infants younger than 9 months of age, the vaccination should be considered for unprotected household members or any person in close contact with a pregnant woman or a very young baby. Additionally postpartum catch-up vaccination of susceptible persons is another the large number of subjects in each group, it is thus reasonable to believe that our results provide a true idea of the inverse correlation that may exist between passive immunity and severity of varicella complications in infants below one year of age.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Febrile seizure in two published [44,50] and all unpublished clinical trials was reported as one of serious adverse events (SAEs), while it was not limited to SAE in other published trials. Vaccine related febrile seizure was defined as febrile seizure diagnosed by the investigator to have a causal relationship to investigational vaccine.…”
Section: Definition Of Febrile Seizurementioning
confidence: 95%
“…Children in 17 clinical trials [27][28][29][30]33,35,37,38,40,41,[44][45][46]48,50] received two doses of MMRV vaccines. Jadad scores were equivalent to 2 or 3 in all the clinical trials listed in Table 1, except the study by Rüger, et al [44], which was not a RCT and was not included in the quantitative meta-analysis. Considering little difference between the quality of included RCTs, there was not a stratified analysis by ranking.…”
Section: Description Of Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…As there was no interference of the hexavalent vaccine with the immune response of ProQuad ® administered as a first dose, no interference is anticipated if ProQuad ® is administered as the second dose of the MMRV vaccination regimen. Similarly, the safety profile is not expected to be affected by concomitant administration, particularly as the second dose of ProQuad ® has been shown to have a better overall safety profile than the first dose [28].…”
Section: Tablementioning
confidence: 98%